Status Kepemilikan Bangunan dan Sarana di Atas Tanah Objek Build, Operate, And Transfer Dalam Kepailitan Pemilik Tanah - Michelle Yaputri Budiman (Fakultas Hukum Universitas Surabaya, 2018)
Capital and land constraints encourage parties to establish mutually supportive and profitable cooperative relationships, then manifested in the form of an agreements, one of them by Build, Operate, and Transfer Agreement (BOT). The possibility of a problem in the BOT agreement is quite large, for example when a BOT agreement is in progress, the Land Owner has a debt and can’t afford to pay the debt, then the land owner can be declared bankrupt based on the Commercial Court’s verdict. One of the cases is the bankruptcy of PT. X (as a land owner) in 2014, 21 years before the verdict, which is 1993, PT. X had a BOT agreement with PT. Y (as a builder). The main issues in this thesis are: 1. Are the buildings and the golf courses built by the builder above the debtor’s land which is bound with BOT agreement which the debtor is declared bankrupt before the transfer, including in bankrupt assets?; and 2. What are the legal protection for the builder as the BOT receiver due to the bankruptcy of land owner? This research is a normative legal research uses statute approach, conceptual approach, and case approach. The results of this research is the buildings and all the facilities which are built by the builder are not including in bankrupt assets because Indonesian Land Law adheres to the principle of horizontal separation, so as long as no transfer has occurred the land owner only has the land, the buildings and all things which are built by builder belong to the builder. The legal protection for the builder as the BOT receiver due to the bankruptcy of the land owner are the curator can continue the BOT agreement based on Article 36 Law of Bankruptcy and Suspension of Obligation for Payment of Debts, make a novation, and the builder can file a compensation and then will become a concurrent creditor.